(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
The conversion of cyclic hydrocarbons into linear paraffins represents an important industrial process in modern petrochemical technology. Linear paraffins are widely used as raw materials for detergents, lubricants, fuels, and petrochemical intermediates. This article reviews the fundamental principles, reaction mechanisms, and technological approaches for producing paraffins from cyclic hydrocarbons through catalytic hydrogenation and ring-opening reactions. Special attention is given to reaction conditions, catalysts, and product selectivity. The study highlights the efficiency and industrial relevance of these processes in meeting the growing demand for high-purity paraffins.